Analisis Rantai Pasok Kopi Pada PT Bogor Kopi Indonesia di Bogor - Muhammad Aryo Fachrezi; Lien Febrina; Syavira Nayla Shaumy; Muhammad Daniyal Stis; Agryani Petra Sitorus; Khoirul Aziz Husyairi; Tina Nur Ainun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
PT Kopi Bogor Indonesia is a company that provides coffee plantation products and guidance for coffee farmers in Bogor. This research was conducted using a survey method with primary and secondary data. Primary data was obtained from interviews with the owner of PT Bogor Kopi Indonesia. The analysis method used is qualitative descriptive analysis. The actors in each supply chain include coffee farmers, the head of farmer partners, PT Bogor Kopi Indonesia, PT Aradea Bogor Kopi, and cafes. The performance of this robusta coffee supply chain is measured by tracing the flow of goods, money, and information. The distribution level in the PT Bogor Kopi Indonesia supply chain is level 3 because there are 3 intermediaries from the supplier to the end consumer. The supply chain strategy used is responsive and the distribution strategy uses a warehousing strategy with a FIFO system. The contribution of farmers in the supply chain is 91% and 95%.